ALGORITHM FOR EARLY CANCER DETECTION IN CHILDREN - M. Yu. Rykov; O. A. Manerova; I. A. Turabov; V. V. Kozlov; V. A. Reshetnikov (Сибирский онкологический журнал, 2020)
Background. Over the past decades, there has been a steady increase in the incidence of childhood cancer. The most childhood cancers are detected at advanced stages. The incidence of childhood cancer increased by 12.8 % (from 11.7 per 100,000 in 2007 to 13.2 per 100,000 in 2017) and the prevalence increased by 37.9 % (from 63.9 in 2007 to 88.1 in 2017 per 100,000). The purpose of the study was to develop algorithms for early cancer detection in children.Material and Methods. In the Arkhangelsk region, the algorithm for referring a patient to a consultation with a pediatric oncologist was introduced into pediatric clinical practice in 2016. To evaluate the effectiveness of the algorithm, we compared two groups of patients with histologically verified solid malignant neoplasms. Group I included 49 patients, who received treatment in 2011–15 (before performing the experiment), and group II consisted of 51 patients, who received treatment in the Department of Pediatric Oncology in 2016–18 (the control group).Results. The use of the algorithm for referring a patient to a consultation with a pediatric oncologist led to the increase in the 3-year survival time from 25.04 ± 2.05 months to 30.3 ± 1.57 months (р=0,045). The time parameters of various stages preceding the start of specialized treatment were statistically significantly reduced: the time from the visit of a pediatric oncologist to verification of the diagnosis decreased from 9.0 (7.0; 14.0) to 7.0 (5.0; 9, 0) days (p˂0.001); the time from diagnosis verification to the beginning of specialized treatment – from 12.0 (8.0; 16.0) to 8.0 (6.0; 10.0) days (p˂0.001); the time from the visit of a pediatrician to referral to a pediatric oncologist – from 11.0 (6.0; 17.0) to 2.0 (1.0; 3.0) days (p˂0.001); the time from the visit of a pediatrician until the beginning of specialized treatment – from 23.0 (17.0; 32.0) to 9.0 (8.0; 12.0) days (p˂0.001).Conclusion. The introduction of a structural and functional model for organizing medical care for children with cancer was shown to be effective.